Designing of WS2@NiCoS@ZnS Nanocomposite Electrode Material for High-Performance Energy Storage Applications - Muhammad Imran; Amir Muhammad Afzal; Areej S. Alqarni; Muhammad Waqas Iqbal; Sohail Mumtaz (Crystals)
Researchers are developing innovative electrode materials with high energy and power densities worldwide for effectual energy storage systems. Transition metal dichalcogenides (TMDs) are arranged in two dimensions (2D) and have shown great promise as materials for photoelectrochemical activity and supercapacitor batteries. This study reports on the fabrication of WS2@NiCoS and WS2@NiCoS@ZnS hybrid nano-architectures through a simple hydrothermal approach. Because of the strong interfacial contact between the two materials, the resultant hierarchical hybrids have tunable porosity nanopetal decorated morphologies, rich exposed active edge sites, and high intrinsic activity. The specific capacities of the hybrid supercapacitors built using WS2@NiCoS and WS2@NiCoS@ZnS electrodes are 784.38 C g−1 and 1211.58 C g−1 or 2019.3 F g−1, respectively, when performed at 2 A g−1 using a three-electrode setup. Furthermore, an asymmetric device (WS2@NiCoS@ZnS//AC) shows a high specific capacity of 190.5 C g−1, an energy density of 49.47 Wh kg−1, and a power density of 1212.30 W kg−1. Regarding the photoelectrochemical activity, the WS2@NiCoS@ZnS catalyst exhibits noteworthy characteristics. Our findings pave the way for further in-depth research into the use of composite materials doped with WS2 as systematic energy-generating devices of the future.